Adaptation strategies and new forms of financing for mining and metallurgical enterprises - Rozhnov Ivan; Prokhorov Viktor; Maslova Olga (E3S Web of Conferences)
This study examines the impact of high interest rates set by the Central Bank of the Russian Federation (CBRF) on the financial stability and investment activity of the mining and metallurgical sector. The sharp increase in the CBRF key rate in 2024 reduced access to credit. The research identifies concerning trends such as the suspension of investment projects, contraction of business activities, and a shift by companies toward low-risk financial instruments like deposits. The analysis also considers the compounding effects of global factors, including declining metal prices, uncertainties in the Chinese market, which further exacerbate financial challenges for Russian mining and metallurgical enterprises. The paper reviews various adaptation strategies employed by companies to mitigate the adverse effects of expensive borrowing. Examples include the adoption of digital financial assets, green financing instruments like climate transition bonds, and increased collaboration with junior exploration companies. The findings highlight the importance of diversifying funding sources and developing innovative financial instruments to support the sustainable development of the sector under volatile economic conditions. The study concludes that successful adaptation requires flexibility in strategy, proactive search for alternative financing, and the implementation of innovative solutions to maintain operational efficiency and resilience.